2016
DOI: 10.1016/j.msea.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Atomic size and local order effects on the high temperature strength of binary Mg alloys

Abstract: The solid solution strengthening introduced by Ca (0.6 and 0.9 at.%) and Sn (0.5 to 2.5 at.%) was studied through tensile, compression and stress relaxation tests at room temperature, 373K (100°C) and 453K (180°C) on solution heat-treated and quenched specimens and compared with existing data for binary alloys containing Ca, Sn, Y, Gd, Nd, Zn and Al as well as for AZ91 alloy. At room temperature the solution-hardening rate introduced by Ca and Sn was much higher than that of Al, matching those of Y, Gd and Zn.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 63 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…and Gd were suggested to have the highest potency on developing SRO and therefore significantly increasing the creep resistance of Mg alloys, followed by Nd. Later, research from the same group[124,125] experimentally verified the above hypothesis in terms of the compression and stress relaxation behaviours using binary Mg-M (M denotes the solutes) alloys that were just solid solution treated. It was found that the stress relaxation resistance at 180 C was consistent with the order forming the SRO of solutes.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…and Gd were suggested to have the highest potency on developing SRO and therefore significantly increasing the creep resistance of Mg alloys, followed by Nd. Later, research from the same group[124,125] experimentally verified the above hypothesis in terms of the compression and stress relaxation behaviours using binary Mg-M (M denotes the solutes) alloys that were just solid solution treated. It was found that the stress relaxation resistance at 180 C was consistent with the order forming the SRO of solutes.…”
mentioning
confidence: 88%
“…Hence, the SRO hypothesis needs further investigation. But, previous studies [124][125][126] indicated that solid solution strengthening of dilute Y, Gd and Nd solutes may play a more important role than precipitation strengthening in improvement of the creep resistance of Mg alloys.…”
Section: Solid Solution Strengtheningmentioning
confidence: 98%
See 2 more Smart Citations